Structural changes in the building materials industry and their factors - S. V. Sianin (Вестник университета)
In order to develop and improve competitiveness of the building materials industry, it is necessary to identify the main structural changes and determine their factors. The study of the structural changes and their factors will reveal the relationship with the main directions of development of the industry of the Russian Federation (hereinafter referred to as RF), which will determine the important place of the building materials in the complex system of its transformation. An analysis of the literature on the creation of intersectoral ecosystems is conducted. Internal and external factors influencing the structure of the building materials industry are determined. An analysis of structural changes in this industry (using cement-containing and related products as an example) for 2017–2022 is conducted. A comparison is made of the ratio of growth rates of production volumes of the cement-containing and related products in 2022 relative to 2017. The properties of elements of the building materials industry are determined depending on the share of the main resource in production. Provisions are formulated for the creation of intersectoral ecosystems, which will be based on the production of the construction industry with a highly diversified resource base. Further research directions are determined to formulate a new mechanism for the resource base of the construction industry to achieve the goals and objectives of the industrial policy of the RF.